High-precision finite element analysis of elastoplastic dynamic responses of super-high-rise steel frames. - Ohsaki, Makoto (Earthquake engineering & structural dynamics.)
A new framework is presented for analysis of dynamic collapse behavior of steel frames using large-scale parallel finite element method based on the domain decomposition method. The analysis software is based on ADVC as a part of the E-Simulator that takes advantage of recent development of computer science and high-performance parallel computing in computational mechanics. By making an analysis model with fine meshing, a complicated sequence of local buckling of columns and beams can be simulated. Numerical results are shown for dynamic collapse analysis of single-story and 5-story frame models to show that the global and local behaviors are simultaneously simulated by a high-precision finite element analysis. Eigenvalue analysis is also carried out for a 31-story frame to demonstrate that dynamic analysis can be carried out for a structure discretized to solid elements with more than 70 million DOFs.